The Visionary Leadership of Headmaster in Improving School Achievement - Achmad Humaidi; Badrul Mudarris; Muhammad Muhammad (Yayasan Avicenna, 2022)
This research is about the leadership of a visionary principal in improving school achievement at SMA Nurul Jadid Paiton, Probolinggo. The background of this study is based on the growing need for transformational leadership in schools to enhance institutional quality and student performance. In an era of competitive education, the role of school principals is no longer limited to administration but extends to becoming agents of change who can inspire, direct, and lead innovation within their institutions. Therefore, this study aims to explore how visionary leadership contributes to improving overall school achievement, including academic performance, institutional reputation, and stakeholder engagement. This study employed a qualitative approach with a case study design to capture the depth and complexity of leadership practices. Data collection was conducted through in-depth interviews with selected informants using a purposive sampling technique. The findings reveal that the visionary principal's leadership in improving school achievement is reflected in three main themes; 1) Scientific Integrity emphasizing ethical academic standards and continuous learning; (2) Consumption Experiences. Enhancing the quality of school services and facilities as perceived by students and parents; and 3) Social Influences. Establishing strong community networks and alumni involvement in school development. These aspects collectively contribute to shaping a school culture that supports sustainable achievement.